Spillovers from foreign firms through worker mobility: An empirical investigation - Holger Görg; Eric Strobl (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
While there has been a large empirical literature on productivity spillovers from multinationals this literature treats the channels through which these spillover effects work as a black box. The innovation of this paper is to investigate whether spillovers occur via worker mobility. We use data on whether or not the owner of a domestic firm has previous experience in a multinational, and relate this information to firm level productivity. Our results suggest that firms which are run by owners that worked for multinationals in the same industry immediately prior to opening up their own firm are more productive than other domestic firms.
Keywords: J61; F23; F21; 330; Foreign direct investment; Spillovers; Worker mobility; Training; Arbeitsmobilität; Multinationales Unternehmen; Spillover-Effekt; Unternehmensentwicklung; Verarbeitendes Gewerbe; Ghana